Correlation between Flatfoot and Postural Balance in Children Aged 7-12 Years - Ramadhani, Alinda Nur; Romadhoni, Dea Linia (FISIO MU: Physiotherapy Evidences, 2024)
Introduction: Flatfoot is characterized by a decrease or flattening of the medial longitudinal arch of the foot. Flatfoot can also occur physiologically, which is then referred to as flexible flatfoot. Normally the arch of the foot is formed in the first five years of life at an age range of 2-6 years. The arch of the foot plays an important role in absorbing ground reaction forces and supporting the body's weight during activities. Methods: The research design uses a cross-sectional study approach, which aims to find or study the relationship between flatfoot and balance in children aged 7-12 years. A total of 32 respondents aged 7-12 years who met the inclusion criteria were obtained through flatfoot examination using a wet footprint examination and balance examination using the Pediatric Balance Scale. Result: The results of the Pearson Correlation Test show a significance value of 0.031 (p<0.05) between the variables flatfoot and balance, which means there is a relationship between flatfoot and balance in children aged 7-12 years. Conclusion: The correlation coefficient value is 0.383, which means that the strength of the relationship between the two variables is quite strong with the direction of the relationship being positive, which means that the higher the degree of flatfoot in the child, the lower the child's balance.